African Honey Bee: What You Need to Know - H. Glenn Hall; Catherine Zettel-Nalen; James D. Ellis (EDIS)
African honey bees entered the United States in the early 1990s and have since spread throughout the Southwest and Southeast, including parts of Florida. Compared to European bees, African bees are highly aggressive when disturbed and are more likely to sting humans and animals.  This revised 6-page fact sheet covers the history and distribution of African honey bees in the Americas and explains how beekeepers and residents can manage their interactions with these bees. Written by H. Glenn Hall, Catherine Zettel-Nalen, and James D. Ellis, and published by the UF Department of Entomology and Nematology, December 2014.